JENIS KOHERENSI KALIMAT DALAM RUBRIK CRIME STORY SURAT KABAR TRIBUN JAMBI EDISI MARET 2019 - Firman Tara; M. Arjun (Universitas Batanghari, 2019)
This study aims to describe the type of coherence in the column of crime story of Tribun Jambi March edition. This research uses qualitative descriptive method. Research Data is obtained by using documentation techniques. The data on this research is a sentence which contains of types of coherence, namely; cause and effect, addition, process, spatial, and indefinites. The source of the data is in the form of news text in the column of crime story of Tribun Jambi newspaper. Based on the results of the data anaylsis, it is found that there are 543 types of coherence in the crime story column of Tribun Jambi March edition 2019. There are 20 quotations of cause and effect which are characterized by three conjunctions, such as maka, jadi, and, sebaliknya. There are 293 types of addition coherence which are characterized with six conjunctions i.e. dan, selain itu, baik, maupun, serta, and di samping itu. There are 128 types of process coherence which are characterized with two conjunctions namely dengan and tanpa. There are 83 types of spatial coherence which are characterized by six conjunctions i.e., lalu, kemudian, setelah itu, pada saat itu, sebelumnya, and sementara itu. There are 19 quotations of indefinites coherence which are marked with four conjunctions i.e. bukan hanya, bahkan, selanjutnya, and lalu. Thus, it is found that the addition coherence as the dominant type which occurs in the column of crime story in Tribun Jambi newspaper March edition 2019. While the least coherence found in the data is indefinites coherence.